해방기 오장환 시에 나타난 예세닌 시의 수용 양상 연구 - 한세정(Han, Se-Jeong) (한국시학연구, 2015)
이 논문은 해방기 오장환 시에 나타난 예세닌 시의 수용 양상을 살피고 그것이 그의 시 세계에 미친 영향을 밝히는 것을 목적으로 한다. 해방 직후 오장환이 번역한 『에세-닌 시집』은 해방기 오장환의 시적 모색을 살필 수 있는 중요한 단초를 제공한다. 창작시집보다도 먼저 간행된 『에세-닌 시집』은 오장환이 ‘해방기’의 특별한 역사적 인식 아래서 기획적으로 번역한 창작물로 주목된다. ‘러시아 혁명’과 ‘식민지 해방’이라는 역사적 공감대 속에서 오장환에게 예세닌 시는 해방기 시단에 대응될 수 있는 문학적 가능성을 보여준 전범으로서 인식되었을 것으로 예상된다. 오장환 시에 나타난 예세닌 시의 수용 양상은 예세닌 시에서 ‘모스크바’로 표상되는 ‘내 나라’에 대한 인식과 관련되어 나타난다. 오장환은 ‘모스크바’ 표상을 통해 혁명기 러시아 현실에 적극적인 인식을 보여준 예세닌 시의 특징을 수용함으로써 해방 이후 ‘병든 서울’로 표상되는 조선의 현실을 직시하고 성찰하는 태도를 심화한다. 하지만 오장환의 시는 ‘모스크바’가 표상하는 소비에트 러시아의 현실에 부합하지 못하고 절망적 태도를 보이는 예세닌 시와는 달리 ‘병든 서울’이 표상하는 해방 후 현실을 목도하면서 새롭게 나아가야 할 방향성을 모색하는 변별점을 지닌다. 오장환 시에 나타난 또 다른 예세닌 시의 수용 양상은 고향 모티프로 이루어진 시편에서 확인된다. 해방기 오장환은 예세닌의 귀향 시편에 나타난 고향 모티프를 변주하여 ‘돌아가야 할 땅’으로 고향을 환기시키고 이념적 공간으로서 고향의 의미를 변주하고 확장한다. 예세닌 시에서 화자가 돌아온 고향의 현실에 절망하고 있었다면 오장환 시의 화자는 새로운 가능성을 지닌 공간으로서 고향을 인식한다. 오장환의 해방기 시에서 고향은 화자의 이념이 성취될 수 있는 긍정적인 공간으로 제시된다. 오장환은 『에세-닌 시집』을 출간함으로써 해방 이후 자신의 문학적 입지점과 시적 전략을 명확히 제시하고 있었으며 예세닌 시를 독자적으로 수용함으로써 시 세계를 확장하는 양상을 보인다. 오장환은 예세닌 시를 통해 ‘지금 여기’에 대한 인식을 심화하는 동시에 그가 비판적으로 평가했던 예세닌 시의 특징을 쇄신함으로써 현실에 대한 적극적인 시적 방법론을 구축한다. 해방기 오장환 시에 나타난 예세닌 시의 수용 양상은 주체적인 관점에서 예세닌 시를 창조적으로 수용했다는 점에서 그 의의가 발견된다. The purpose of this study was to examine the acceptance patterns of Esenin’s poems in those of Oh Janghwan during the Liberation period and their effects on the poetic world of Oh Janghwan. Esenin’s Collection of Poems, which was translated by Oh Janghwan, offers important clues to understand his poetic searches during the Liberation period. Being published before his collection of creative poems, the Collection attracts attention as a collection of creative works that he translated according to his plan based on the special historical perceptions of Liberation period. He must have taken Esenin’s poems as classics that demonstrated the literary possibilities to respond to the poetical circles during the Liberation period based on the historical consensus of ‘Russian Revolution’ and ‘liberation of colony’. The acceptance patterns of Esenin’s poems in the works of Oh Janghwan are related to Esenin’s perception of “my country” represented by “Moscow.” By accepting the characteristics of poems of Esenin, who exhibited active perceptions of Russian reality during the Revolution through the representation of “Moscow,” Oh Janghwan intensified his attitude of facing squarely and looking back on the reality of Joseon represented by “sick Seoul.” His poems are, however, distinguished from those of Esenin, who failed to correspond to the reality of Soviet Russia represented by “Moscow” and showed a desperate attitude, in that he searched for new directionality in the reality represented by “sick Seoul.” Another acceptance pattern of Esenin's poems in Oh Janghwan’s works is found in his poems based on the hometown motif. Oh Janghwan aroused the significance of hometown as “land to return to” by altering the hometown motif in Esenin’s poems about homecoming and also altered and expanded the meanings of hometown as an ideological space. In Esenin’s poems, the speakers get frustrated with the reality of hometown and fail to fuse with it. In Oh Janghwan’s poems, on the other hand, the speakers perceive the hometown as a space of new possibilities, in which case the hometown is reorganized as a positive space where an ideology can be fulfilled. Oh Janghwan clearly presented his literary positions and poetic strategies after Liberation by publishing Esenin's Collection of Poems and showed the pattern of expanding his poetic world by accepting Esenin’s works independently. He deepened his perception of “right now, right here” through Esenin’s poems and established a more active poetic methodology about the reality by renovating the characteristics of Esenin’s poems that he was critical of. The acceptance patterns of Esenin’s poems in the poems of Oh Janghwan during the Liberation period claim their significance in that he accepted Esenin’s poems in a creative manner from an independent perspective. KCI Citation Count: 10